Entropy and Exergy in Renewable Energy - Wang, Lin-Shu; Cao, Wenping; Hu, Shu-Bo (IntechOpen, 2022)
Lovelock identified Newcomen's atmospheric steam engine as the start of Anthropocene with these words: "...there have been two previous decisive events in the history of our planet. The first was ... when photosynthetic bacteria first appeared [conversing sunlight to usable energy]. The second was in 1712 when Newcomen created an efficient machine that converted the sunlight locked in coal directly into work." This book is about the necessity of energy transition toward renewables that convert sunlight diurnally, thus a sustainable Anthropocene. Such an energy transition is equally momentous as that of the kick start of the second Industrial Revolution in 1712. Such an energy transition requires "it takes a village" collective effort of mankind; the book is a small part of the collective endeavor.